SNACK BAR BUSINESS INNOVATION TO SUBSTITUTE OKARA FLOUR AND BLACK RICE FLOUR (Oryza sativa L. Indica) AS SNACKS FOR OBESE TEENAGERS - Sabita, Ailsa Aurellia; Pudjirahaju, Astutik; Soelisyorini, Dwie (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
The Central Statistics Agency (BPS, 2021) the prevalence of obesity in 2018 reached 20.60% of men and 44.40% of women. Snack bars are bar-shaped snacks made from cereals or nuts that have high fiber content as an alternative to delaying hunger. The purpose of the study was to analyze the innovation of a snack bar business substituting okara flour and black rice flour (Oryza Sativa L. Indica) as a snack for obese adolescents including production aspects, financial aspects, SWOT analysis, and buyer responses. The type of research is exploratory to understand business innovation by previous researchers' food products. The results of the study show that the production aspects of packaging and labels have followed the Food and Drug Supervisory Regulation (BPOM) Number 31 of 2018. The financial aspect of the Black Soy Delight snack bar earned a profit of IDR 158,480 from the sale of 50 pcs with a total revenue of IDR 600,000. The SWOT analysis of the business position shows quadrant I which means it supports an aggressive strategy which means that business innovation can be carried out well and has great opportunities. The questionnaire results obtained from buyer responses to the level of taste satisfaction 50% (very good), label 76% (very good), packaging 72% (very good), and price 76% (very good). Based on the results of the study, snack bar products have a large market opportunity with the support of packaging design that complies with BPOM, good financial benefits, and positive responses from consumers to quality and price.